SOSIALISASI BAHAYA MINUMAN KERAS BAGI REMAJA - Titik Nurbiyati (UII, 2014)
Basically modernization of the technological advances that result in changes quitecomplex. One of the effects of modernization of this new social and economic factors isquite real in our communities is the misuse of liquor in teenagers. The liquor is any kindof strongdrink, so that by drinking it becomes lost consciousness. Abuse of liquor isnow a problem that is developing in the world of youth and showed an upward trendfrom year to year. Residents in theDusunKregangan RW 2 Subdistrict Juwiring has ahabits to consume alcohol either on a daily basis and on a great show. Expectedknowledge residents can grow and people can avoid to consume liquor. For residentswho already have tried, is expected to stop the consumption of liquor.